Integrated ontology-based approach with navigation and content representation for health care website design. (March 2022) - Chang, Te-Min; Kao, Hao-Yun; Wu, Jen-Her; Hsiao, Kai-Wen; Chan, Te-Fu
Highlights: Ontology-based approach is effective for developing a health care website with high usability. Ontology-based website supports online seeker knowledge-acquisition tasks more effectively than does a text-based website. Ontology can be used to found website information architecture of health care knowledge. Navigational mechanisms incorporated with ontology can facilitate task-based wayfinding navigation. Navigational and representational design mechanisms can be used to display contextual representations.